Optical and Electromagnetic Tracking Systems for Biomedical Applications: A Critical Review on Potentialities and Limitations - Sorriento, Angela; Porfido, Maria Bianca; Mazzoleni, Stefano; Calvosa, Giuseppe; Tenucci, Miria; Ciuti, Gastone; Dario, Paolo (IEEE reviews in biomedical engineering, 2020)
Optical and electromagnetic tracking systems represent the two main technologies integrated into commercially-available surgical navigators for computer-assisted image-guided surgery so far. Optical Tracking Systems (OTSs) work within the optical spectrum to track the position and orientation, i.e., pose of target surgical instruments. OTSs are characterized by high accuracy and robustness to environmental conditions. The main limitation of OTSs is the need of a direct line-of-sight between the optical markers and the camera sensor, rigidly fixed into the operating theatre. Electromagnetic Tracking Systems (EMTSs) use electromagnetic field generator to detect the pose of electromagnetic sensors. EMTSs do not require such a direct line-of-sight, however the presence of metal or ferromagnetic sources in the operating workspace can significantly affect the measurement accuracy. The aim of the proposed review is to provide a complete and detailed overview of optical and electromagnetic tracking systems, including working principles, source of error and validation protocols. Moreover, commercial and research-oriented solutions, as well as clinical applications, are described for both technologies. Finally, a critical comparative analysis of the state of the art which highlights the potentialities and the limitations of each tracking system for a medical use is provided.